MULTIFUNCTIONAL SOLAR SYSTEMS FOR HEATING AND COOLING - Doroshenko A.V.; Silich S.S. (Problems of the Regional Energetics, 2010)
The basic circuits of multifunctional solar systems of air drainage, heating (hot water supply and heating), cooling and air conditioning are developed on the basis of open absorption cycle with a direct absorbent regeneration. Basic decisions for new generation of gas-liquid solar collectors are developed. Heat-mass-transfer apparatus included in evaporative cooling system, are based on film interaction of flows of gas and liquid and in them, for the creation of nozzle, multi-channel structures from polymeric materials and porous ceramics are used. Preliminary analysis of multifunctional systems possibilities is implemented.